Promoting interest, positive emotions, and knowledge using augmented reality in a museum setting. Issue 3 (3rd July 2021) - Kennedy, Alana A. U.; Thacker, Ian; Nye, Benjamin D.; Sinatra, Gale M.; Swartout, William; Lindsey, Emily
ABSTRACT: Informal learning environments, such as museums, provide unique opportunities for science learning. They are deliberately designed to impact public understanding of science and shape visitors' attitudes and behaviors. As a developing technology, augmented reality (AR) offers the transformative potential to support museums' educational missions by enhancing visitors' experience, thereby creating effective conditions for learning and personalized interactions with science. We implemented an AR-enhanced exhibit at the La Brea Tar Pits (LBTP) to reduce scientific misconceptions and explore the role of interest and emotions around science and AR technology as it related to learning and knowledge revision. Using a pretest-posttest design, 62 adults completed an AR experience that addressed two scientific misconceptions related to the consistency of tar and frequency of large animal entrapment. We found that participants had significantly fewer misconceptions at posttest than at pretest. Participants also reported higher levels of interest in science content than AR technology and discriminated between emotions they experienced with regard to science content and AR technology. Feelings of curiosity predicted knowledge revision and interest in both science content and AR technology. These findings may be useful for museums and other science communicators seeking to create AR interventions that support learning and conceptual change.